Crack sliding model for non-shear FRP-reinforced slender concrete elements under shear - El-said, Amr; Awad, Ahmed; El-Sayed, Taha A.; Özkılıç, Yasin Onuralp; Deifalla, A.; Tawfik, Maged (Frontiers in Materials, 2023)
Fiber reinforced polymer (FRP)-reinforced concrete (RC) elements fail under one-way shear ina devastating and complicated mannerwith no adequate warning. For a few decades, research effort has yielded several pioneering works in this area; however, there is a lack of agreement among researchers regarding mechanically based models. Thus, in the current study, a plas-ticity-based model is developed for FRP-RC elements under shear.Firstly, a selected model was assessed on the merit of accuracy, consistency, and safety with respect to an extensive experimental database. Secondly, a plasticity-based model (i.e., crack shear sliding model) is adapted, refined, and proposedfor FRP-RC elementsunder one-way shear.The two proposed models were found to be reliable and more accurate with respect to the selected existing me-thods. Modeling of the FRP axial rigidity is more consistent compared to only young’s modulus with respect to the experimental database. Several concluding remarks on the selected existing models were outlined and discussed, which is helpful for the future development of these models and design codes.